Interpretation of Debt-to-Equity Conversion for Goods Purchase Transactions Under POJK 14/2019 - Muhammad Rausyan Fikry; Iwan Erar Joesoef; Diani Sadia Wati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Interpretation of debt-to-equity swap provisions for goods purchase transactions as stipulated in the Financial Services Authority Regulation (POJK) Number 14/POJK.04/2019 concerning Affiliated Transactions and Conflicts of Interest in Certain Transactions. The principle of openness and fairness in transactions between affiliated parties, including in the context of debt-to-equity swaps. However, this provision does not explicitly regulate the conversion of debt arising from goods purchase transactions, thus creating room for legal interpretation regarding whether business debt from operational activities can be converted into equity participation through the issuance of new shares. This study aims to analyze the implementation of debt-to-equity conversion as a financial restructuring strategy, with a focus on legal certainty and protection of public shareholders based on POJK 14/2019. The study uses a normative legal approach with the method of statutory regulations and case studies on PT SLJ Global Tbk. The results of the study indicate that PT SLJ Global Tbk has complied with the formal procedures of POJK 14/2019, including information disclosure, GMS approval, and unaffiliated creditor criteria. However, the conversion of business debt creates legal ambiguity due to the lack of clarity as to whether the debt meets the definition of “loan” in POJK 14/2019. In addition, the dilution of public shares by 34.32% without adequate protection mechanisms indicates a lack of legal certainty. The study recommends normative interpretation and strengthening of regulations to ensure fairness and legal certainty in the practice of debt conversion. Keywords: ; ; ; ;